ANALISIS DATA PRODUKSI KELAPA SAWIT DI LAHAN GAMBUT PT SINAR GUNUNG SAWIT RAYA KECAMATAN MANDUAMAS KABUPATEN TAPANULI TENGAH - Lumban Tobing, Herdianta; Pratomo, Bayu (Jurusan Kehutanan, 2022)
Oil palm is one of the essential vegetable oil-producing plants. Moreover, palm oil is a good trade commodity, and in the future, it is believed that palm oil will not only be able to produce various products such as butter, cooking oil, or soap but also can be a substitute for fuel oil. This study aims to compare crop production in coastal and non-coastal peatlands. This study uses secondary data, including production, rainfall, and fertilization data from the last five years. The results show that Block F2 (on the beach) has the highest production, with a value of 2,442,572 kg/ha. In comparison, Block B2 (non-coastal) has a lesser amount, with a value of 1,818,710 kg/ha.